(untitled) (Research, Society and Development, 2020)
The present research aims to analyze the historical synopsis of the penalty, its theories, as well as offer notes regarding the prison and the reality of the Brazilian prison system. In this perspective, this article, through exploratory research, of qualitative nature, deductive method, collection of bibliographic-documental data, proceeded in order to carry out an analysis about the critical situation of Brazilian prisons, marked by overcrowding and constant violations of Human Rights, as well as the lack of minimum conditions for serving the sentence in a dignified manner, often making it impossible for the prisoner to re-socialize. It should also be noted that there is an alarming mark in the recidivism rates, characterizing a profound bankruptcy of the prison and penal system, considering that the results are the increasing increase in violence, crime and the feeling of insecurity experienced by the whole society that, although it has witnessed a significant evolution, it still experiences problems in the social environment. Under this bias, it appears that criminal organizations, in addition to being located in more vulnerable locations within a society, also install themselves within the prison system, promoting riots and rebellions, thus causing major crises, which must be managed by the very prison system. In this sense, the importance of carrying out the study of Crisis Management is evidenced, being necessary, as in any other branch of scientific knowledge, the establishment of certain basic principles and definitions for greater doctrinal uniformity.